The economic performance of mango integrated pest management practices at different scales of production - Mulungu, Kelvin; Muriithi, Beatrice Wambui; Kassie, Menale; Khamis, Fathiya Mbarak (Frontiers in Insect Science, 2023)
Integrated pest management (IPM) strategies are being promoted to suppress tephritid fruit fly infestation and reduce economic damage in mango production. However, research on their economic performance across different mango production scales (measured by the number of mango trees) is limited. This study estimated the economic benefits of IPM practices (parasitoids, orchard sanitation, food bait, biopesticides, male annihilation technique, and their combinations) in Kenya's small-, medium-, and large-scale mango production systems. We used the value-cost ratio (VCR) and net present value methods to estimate the heterogeneous economic performance of IPM practices using data from two unique farm surveys. On average, all IPM practices were profitable across various production scales. However, we found that these practices were more profitable for medium-scale farmers than for small-and large-scale farmers. The results show that farmers need a minimum of 9-17 trees, depending on the practice, to break even and that there are little to no economic benefits in using IPM practices for farmers with more than 320 mango trees. The male annihilation technique was the most adopted practice and profitable, with a VCR of 36. Overall, we find significant heterogeneity in the profitability of IPM practices across different scales of production. The lack of profitability of IPM on large-scale farms remains unclear and warrants further investigation.